Three new species of Cloacininae (Nematoda: Strongyloidea) parasitic in Dorcopsis muelleri (Schlegel, 1866) from Papua and Salawati island, Indonesia - Dewi, Kartika; Purwaningsih, Endang (Zootaxa, 2020)
Three new species of Cloacininae are described from Dorcopsis muelleri obtained from Salawati Island and Kaimana, Papua. Cloacina woworae sp. nov. differs from all congeners by having postero-lateral and medio-lateral rays not fused and the esophagus wider anterior to the nerve ring. Compared to its congeners, C. beveridgei sp. nov. resembles C. caballeroi Mawson, 1977, C. cretheis Beveridge, 2002, C. erigone Beveridge, 2002, and C. syphax Beveridge & Speare, 1999 in the morphology of the dorsal ray.  However, C. beveridgei has distal segments of sub-median papillae longer than the proximal segments. This character differentiates it from C. caballeroi, C. cretheis, and C. erigone, which have the distal segment of the sub-median papilla shorter than the proximal. Furthermore, this new species can be distinguished with C. syphax in having a shorter vagina vera and in the shape of the anterior region of the vagina. Cervonemella kaimanaensis sp. nov. differs from Ce. reardoni, the sole species in the genus Cervonemella, in the shape and longer vagina, shorter and slender tail, shorter position of vulva from posterior end and longer spicules.